A portable electrochemical immunosensor for rapid detection of trace aflatoxin B1 in rice. Issue 3 (18th December 2015) - Li, Zhanming; Ye, Zunzhong; Fu, Yingchun; Xiong, Yonghua; Li, Yanbin
Abstract : To explore the possibility of achieving rapid and in situ detection of aflatoxin B1 (AFB1 ), a portable biosensing instrument consisting of an impedance detector and a 3D-printed USB-compatible sensor chip was developed. Abstract : To explore the possibility of achieving a rapid and in situ detection of aflatoxin B1 (AFB1 ), a portable biosensing instrument consisting of an impedance detector and a 3D-printed USB-compatible sensor chip was developed. In this study, we proposed an electrochemical biosensor based on screen-printed interdigitated microelectrodes (SPIMs) and a portable detector to achieve low-cost, highly selective and sensitive detection of AFB1 in rice. Under optimized conditions, the immunosensor provided a detection limit of 5 ng mL −1, which was below the allowable concentration. The total detection time including incubation was less than 1 h. The results obtained from this developed portable detection system were comparable to those from a commercial electrochemical station in the laboratory. Hence, the portable detector offers new tools for detection of a wide variety of analytes in clinical and environmental samples.